Practicality of Local Wisdom-Based Science E-Modules Using Problem-Based Learning for Critical Thinking and Digital Literacy - Windiarti Pratiwi Putri; Muntari Muntari; Lalu Rudyat Telly Savalas (Indonesian Journal of Educational Innovation, 2026)
The integration of technology and local wisdom in science learning has become increasingly important to enhance student engagement and understanding. This study aimed to develop and evaluate the practicality of a Science E-Module based on Problem-Based Learning (PBL) and a local-wisdom approach for high school students. The study employed a development research design with limited trials, involving Classroom implementation observations, teacher and student response questionnaires, and data analyzed using descriptive quantitative techniques. The results showed that the Classroom implementation reached 92% (very well implemented), teacher responses averaged 93% (very practical), and student responses averaged 87% (very practical), indicating high engagement and usability. It can be concluded that the developed E-Module is practical and supports effective learning by promoting independent learning, critical thinking, and digital literacy. These findings suggest that integrating PBL and local wisdom through digital modules can be an innovative strategy to improve science learning and is recommended for broader implementation in similar educational contexts.